Advanced Applications of Pozzolan-Derived Silica: Hydrophobic Agent Synthesis - Desfitri, Erda Rahmilaila; Mustikaningtias, Endah; Rizaldi, Fajri Akbar; Sari, Ellyta; Desmiarti, Reni (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
The Sumatera Barat province of Indonesia, particularly Padang Pariaman Regency, is rich in pozzolan, a natural resource characterized by high silica (SiO) and alumina (AlO) content. Despite its abundance, pozzolan remains underutilized, primarily used in conventional applications such as cement substitutes and brick production. This study investigates the extraction, purification, and application of pozzolan-derived silica for advanced industrial uses, focusing on synthesising hydrophobic materials. Silica was extracted from pozzolan using alkali and acid treatments, achieving a high-purity cristobalite phase with 93.86% SiO content based on the X-ray diffraction (XRD) and X-ray fluorescence) XRF analysis. The cristobalite phase was combined with polydimethylsiloxane (PDMS) to develop a hydrophobic agent. Hydrophobic performance was evaluated using water contact angle (WCA) measurements, with two coating methodsswab coating and dip-coatingemployed to test the materials. Results revealed that the cristobalite phase achieved the highest hydrophobicity when applied via dip-coating, reaching a WCA 114. Fourier Transform Infrared (FT-IR) analysed the characteristics of a hydrophobic compound. Furthermore, varying PDMS concentrations influenced hydrophobic performance, with 0.4 grams of PDMS yielding the optimal WCA of 105.31 before diminishing returns were observed at higher concentrations due to aggregation effects. This research demonstrates the viability of pozzolan-derived silica as a sustainable and cost-effective raw material for hydrophobic agent synthesis. The findings highlight its potential applications in advanced industries, including water-repellent coatings, glass, ceramics, and catalysts. By advancing the utilization of natural pozzolan resources, this study contributes to sustainable material development and aligns with global efforts to enhance resource efficiency and innovation.